Towards Reinvigorating Academic Library Use Data Capabilities: a Library and Information Science Senior Student Workshop Experience - Sant-Geronikolou, Stavroula; Koulouris, Alexandros; Kouis, Dimitrios (Journal of Integrated Information Management, 2018)
Purpose - This paper seeks to encourage reflections on the extent to which a one-shot workshop can help about-to-be information Professionals understand and appreciate the gamut of complexities and challenges associated with library position in the emerging Learning Analytics (LA) ecosystem. Design/methodology/approach – It focuses on the description of the experience in organizing a workshop at the Department of Archival, Library & Information Studies (ALIS) of the University of West Attica. Building upon desk and primary research findings, organizers envisioned providing a valuable opportunity for senior students to collaboratively help identify the hidden value of student generated data for the support of their success and retention. Analyses of lessons learned, student viewpoints and recommendations for the future, all aim contributing knowledge to the meta-community of Higher Education library professionals that are exploring ways to streamline their smooth integration into the educational process taking full advantage of new ICT capabilities. Findings - Students seemed to have quickly developed a substantial understanding of risks and opportunities involved in this type of innovation as reflected on detected differences between a set of pre and post-workshop survey indicators. Furthermore, student evaluations on workshop design, delivery and content quality have provided valuable input on its usefulness and a set of recommendations for change. Originality/value - It presents and analyses observations of the first Greek LIS community initiation experience to current Learning Analytics landscape, a topic germane to university libraries that could eventually influence New Information Professionals’ mindset and aspirations.